Effect of annealing temperature on structural, electrical and optical properties of spray pyrolytic nanocrystalline CdO thin films - Azizar Rahman, M.; Khan, M.K.R. (Materials science in semiconductor processing, 2014)
Nanocrystalline CdO thin films were prepared onto a glass substrate at substrate temperature of 300°C by a spray pyrolysis technique. Grown films were annealed at 250, 350, 450 and 550°C for 2.5h and studied by the X-ray diffraction, Hall voltage measurement, UV-spectroscopy, and scanning electron microscope. The X-ray diffraction study confirms the cubic structure of as-deposited and annealed films. The grain size increases whereas the dislocation density decreases with increasing annealing temperature. The Hall measurement confirms that CdO is an n-type semiconductor. The carrier density and mobility increase with increasing annealing temperature up to 450°C. The temperature dependent dc resistivity of as-deposited film shows metallic behavior from room temperature to 370K after which it is semiconducting in nature. The metallic behavior completely washed out by annealing the samples at different temperatures. Optical transmittance and band gap energy of the films are found to decrease with increasing annealing temperature and the highest transmittance is found in near infrared region. The refractive index and optical conductivity of the CdO thin films enhanced by annealing. Scanning electron microscopy confirms formation of nano-structured CdO thin films with clear grain boundary.